Status sołectwa z perspektywy atrybutów związku samorządowego - Lisowski, Piotr; Ostapski, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
A village (civil parish) is a body of public administration that — even though in the current legal situation, it does not fully qualify as an entity of territorial self-government — should be classified as a self-government association (and, at the same time, a public law association). This claim can be justified if the institution of a self-government association is interpreted flexibly and a village (civil parish) is shown to be characterised by the necessary minimum of the attributes related to corporatisation and self-governance.
Keywords: village (civil parish); self-government association; public law association; corporate nature; self-governance